The Influence of Technological Capability on Internationalization Status of Public Universities in Kenya - Kirugumi, Ann Thogori; Theuri, Matthew M.; Magu, David M. (American Journal of Strategic Studies, 2024)
Purpose: The purpose of the study was to determine influence of technological capability on internationalization status of public universities in Kenya. Descriptive research design was used to conduct the study. Methodology: The study employed a descriptive research design. This research study used positivism research philosophy. The target population comprised of all the 31 fully chartered public universities in Kenya. Since the population was small, no sampling was done and a census approach was applied in the study. Primary quantitative data was assembled by administering structured questionnaires. To analyze quantitative data, descriptive analysis, factor analysis and inferential statistics were used. Descriptive analysis comprised of the standard deviations and means. Inferential statistics comprised regression and correlations. Both multiple and linear regressions was used. Coding and analyzing of data was done using Statistical Package for Social Sciences (SPSS 26.0). Tables, diagrams and charts were further used to display the outcomes. Findings: From the study findings technological capability had a statistically significant and positive influence on internationalization status. Unique contribution to theory, practice and policy: Research findings showed that there was need for improvement in the use of online platforms for teaching and research. The study therefore recommends that public universities should therefore invest in upgrading of their online platforms for teaching and research so as to increase on their economies of scale.